Faunistic composition of butterflies (Lepidoptera : rhopalocera) on Pulau Satang Besar and Kubah National Park, Sarawak - Lee, Catherine Sie Hwan. (Universiti Malaysia Sarawak (UNIMAS), 2007)
A study on the faunistic composition of butterflies (Lepidoptera: Rhopalocera) was carried out on Pulau Satang and Kubah National Park, Sarawak in August, September and December, 2006. Overall, a total of 112 species and 369 individuals were collected. Of these, 35 species and 157 individuals from five families were sampled on Pulau Satang Besar while 86 species from 212 individuals were captured at Kubah National Park. Kubah National Park is more speciose in terms of its butterfly composition as compared to Pulau Satang Besar. The butterfly fauna on both Pulau Satang Besar and Kubah National Park are generally not similar in species composition. Only a total of seven species are found at both study sites. Lycaenidae (13 species) was the most speciose family on Pulau Satang Besar while Nymphalidae (72 individuals) represented the most abundant family. In Kubah National Park, Nymphalidae also represented both the most speciose (42 species; 110 individuals) as well as abundant family sampled during this study. The most abundant species on Pulau Satang Besar was Ideopsis juventa sitah (46 individuals) while Ypthima pandocus sertorius (26 individuals) was the most abundant in Kubah National Park. Ideopsisjuventa sitah, a nymphalid species from Pulau Satang is now reported for the first time for Borneo. Two rare butterfly species were also recorded in this study, namely Papilio iswara araspes (Papilionidae) and Eurema simulatrix tecm~ssa (Pieridae) while one endemic species, Paralaxita nicevillei was coHected at Kubah National Park. The papilionid, Troides helena mosyclus, a protected species listed in CITES (Appendix II) was also found on Pulau Satang Besar. The butterfly composition on both Pulau Satang and Kubah National Park is further discussed.